Influence of mutual drag of light and heavy holes on magnetoresistivity and Hall-effect of p-silicon and p-germanium - Boiko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Hall-effect and magnetoresistivity of holes in silicon and germanium are considered with due regard for mutual drag of light and heavy band carriers. Search of contribution of this drag shows that this interaction has a sufficient influence on both effects.